2009
DOI: 10.1007/978-3-642-04355-0_6
|View full text |Cite
|
Sign up to set email alerts
|

The Disagreement Power of an Adversary

Abstract: Abstract. At the heart of distributed computing lies the fundamental result that the level of agreement that can be obtained in an asynchronous shared memory model where t processes can crash is exactly t + 1. In other words, an adversary that can crash any subset of size at most t can prevent the processes from agreeing on t values. But what about the remaining (2 2 n − n) adversaries that might crash certain combination of processes and not others? This paper presents a precise way to characterize such adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 13 publications
1
43
0
Order By: Relevance
“…The result has been generalized to the case of ¬Ω k and k-set consensus in [21]. Delporte et al [22] claimed to have concurrently derived the same result. Anta et al [23] showed that ¬Ω k is the weakest failure detector for solving k-set consensus in the special case of k-resilient environment E k .…”
Section: Related Workmentioning
confidence: 74%
See 1 more Smart Citation
“…The result has been generalized to the case of ¬Ω k and k-set consensus in [21]. Delporte et al [22] claimed to have concurrently derived the same result. Anta et al [23] showed that ¬Ω k is the weakest failure detector for solving k-set consensus in the special case of k-resilient environment E k .…”
Section: Related Workmentioning
confidence: 74%
“…Delporte et al [24] proposed a simulation of a protocol solving a colorless task using ¬Ω k that is similar in spirit to our construction in Sect. 5.…”
Section: Related Workmentioning
confidence: 97%
“…We can think of its generalization to any progress condition on computation processes encapsulated, e.g., in an adversary [19]. Therefore, we can pose questions of the kind: what is the weakest failure detector to solve a task T in the presence of an adversary A?…”
Section: Resultsmentioning
confidence: 99%
“…All tasks that can be solved k-concurrently but not (k + 1)-concurrently (e.g., k-set agreement) are equivalent in the sense that they require exactly the same amount of information about failures (captured by ¬ k ) to be solved in EFD. Note that this characterization covers all tasks, including "colored" ones that evaded any characterization so far [2,19,26].…”
Section: Ramificationsmentioning
confidence: 99%
See 1 more Smart Citation